3-nitroimidazo[1, 2-b]pyridazine as a novel scaffold for antiparasitics with sub-nanomolar anti-Giardia lamblia activity. (August 2022) - Zheng, Yang; Müller, Joachim; Kunz, Stefan; Siderius, Marco; Maes, Louis; Caljon, Guy; Müller, Norbert; Hemphill, Andrew; Sterk, Geert Jan; Leurs, Rob
Abstract: As there is a continuous need for novel anti-infectives, the present study aimed to fuse two modes of action into a novel 3-nitroimidazo[1, 2- b ]pyridazine scaffold to improve antiparasitic efficacy. For this purpose, we combined known structural elements of phosphodiesterase inhibitors, a target recently proposed for Trypanosoma brucei and Giardia lamblia, with a nitroimidazole scaffold to generate nitrosative stress. The compounds were evaluated in vitro against a panel of protozoal parasites, namely Giardia lamblia, Trypanosoma brucei, T. cruzi, Leishmania infantum and Plasmodium falciparum and for cytotoxicity on MRC-5 cells. Interestingly, selective sub-nanomolar activity was obtained against G. lamblia, and by testing several analogues with and without the nitro group, it was shown that the presence of a nitro group, but not PDE inhibition, is responsible for the low IC50 values of these novel compounds. Adding the favourable drug-like properties (low molecular weight, cLogP (1.2–4.1) and low polar surface area), the key compounds from the 3-nitroimidazo[1, 2- b ]pyridazine series can be considered as valuable hits for further anti-giardiasis drug exploration and development. Graphical abstract: Image 1 Highlights: Analogues fusing a nitroimidazole moiety and a PDE inhibitor scaffold were prepared. These compounds were tested in vitro against a panel of protozoal parasites. Against Giardia lamblia, sub-nanomolar IC50 values were determined. PDE inhibition provided no significant contribution to the anti- Giardia potency. High potency with drug-like properties warrants further study of this hit series.